Dual-Acting Compounds Targeting Endocannabinoid and Endovanilloid Systems—A Novel Treatment Option for Chronic Pain Management - Malek, Natalia; Starowicz, Katarzyna (Frontiers in Pharmacology, 2016)
Compared with acute pain that arises suddenly in response to a specific injury and is usually treatable, chronic pain persists over time and is often resistant to medical treatment. Because of the heterogeneity of chronic pain origins, satisfactory therapies for its treatment are lacking, leading to an urgent need for the development of new treatments. The leading approach in drug design is selective compounds, though they are often less effective and require chronic dosing with many side effects. Herein, we review novel approaches to drug design for the treatment of chronic pain represented by dual-acting compounds, which operate at more than one biological target. A number of studies suggest the involvement of the cannabinoid and vanilloid receptors in pain. Interestingly cannabinoid system is in interrelation with other systems that comprise lipid mediators: prostaglandins, produced by COX enzyme. Therefore, in the present review, we summarize the role of dual-acting molecules (FAAH/TRPV1 and FAAH/COX-2 inhibitors) that interact with endocannabinoid and endovanillinoid systems and act as analgesics by elevating the endogenously produced endocannabinoids and dampening the production of pro-inflammatory prostaglandins. The plasticity of the endocannabinoid system and the ability of a single chemical entity to exert an activity on two receptor systems has been developed and extensively investigated. Here, we review up-to-date pharmacological studies on compounds interacting with FAAH enzyme together with TRPV1 receptor or COX-2 enzyme respectively. Multi-target pharmacological intervention for treating pain may lead to the development of original and efficient treatments.